Evaluation of High Density Lipoprotein Cholesterol Concentrations among Elderly Ischaemic Stroke Patients - Ara, Kazi Jannat; Ali Masum, Abu Shams Md Hasan; Saleheen, Md Shafiqus; Kader, Sheikh Abdul; Alam, Sk Mahbub; Shahidullah, Md; Ullah, Akm Anwar; Fatema, Nilufar (University Heart Journal, 2018)
Stroke is an alarming health hazard all over the world as well as in Bangladesh and one of the leading causes of mortality and morbidity. There is a well-established inverse relation between serum concentrations of high density lipoprotein cholesterol (HDL-c) and the risk of coronary heart diseases but it is not a welldocumented risk factor for stroke. This study was done to evaluate of the HLD-c concentration among elderly ischaemic stroke patients. This cross sectional study was conducted in Out Patient department (OPD) stroke clinic and Indoor of the department of neurology, BSMMU, Dhaka from July 2015 to June 2016. A total 200 patients suffering from ischaemic stroke within the range of 61-95 years of age of both sexes with TIA, and hemorrhagic stroke were included. Patient with Stoke after one month of onset, cases with anti-lipid drugs were excluded. Male and female ratio was 1.95:1. Mean age was 68.4±8.24 years. 75 (52.8%) patients had hypertension, 20 (14.1%) had diabetes mellitus,10 (7.0%)patients had atrial fibrillation,8(5.6%)had ischemic heart disease. 44 (31.0%) patients had smoking habit ,mean total cholesterol was 190.7±56.0 mg/dl, mean HDL was36.9±8.4mg/dl, mean LDL was123.9±38.8mg/dl and mean Triglyceride was 175.9±70.5 mg/dl. HDL level gradually decreased according to the increment of age. HDL-c is low in elderly ischaemic stroke patient. University Heart Journal Vol. 13, No. 1, January 2017; 8-12